2022
DOI: 10.1055/a-1922-6778
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Ultrasound – EFSUMB Training Recommendations for the Practice of Medical Ultrasound in Europe

Abstract: Different surgical and medical specialists increasingly use head and neck ultrasound and ultrasound-guided interventions as part of their clinical practice. We need to ensure high quality and standardized practice across specialties, and this position paper of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) describes the training requirements for head and neck ultrasound. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…However, US is an operator‐dependent imaging modality, and competency in head and neck US should be ensured among the clinicians conducting US for independent practice 1 . The American Institute of Ultrasound in Medicine and the European Federation of Societies for Ultrasound In Medicine and Biology recommend that physicians complete formal US courses as an essential part of training 9,10 . Still, only a few countries have incorporated formal ultrasound training into their otolaryngology residency programs 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, US is an operator‐dependent imaging modality, and competency in head and neck US should be ensured among the clinicians conducting US for independent practice 1 . The American Institute of Ultrasound in Medicine and the European Federation of Societies for Ultrasound In Medicine and Biology recommend that physicians complete formal US courses as an essential part of training 9,10 . Still, only a few countries have incorporated formal ultrasound training into their otolaryngology residency programs 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 The American Institute of Ultrasound in Medicine and the European Federation of Societies for Ultrasound In Medicine and Biology recommend that physicians complete formal US courses as an essential part of training. 9 , 10 Still, only a few countries have incorporated formal ultrasound training into their otolaryngology residency programs. 11 A study from the United States found strong interest in surgeon‐performed ultrasound among 78% of the otolaryngology residents, while only 24% had attended a formal ultrasound course.…”
Section: Introductionmentioning
confidence: 99%
“…The American Institute of Ultrasound in Medicine mandates that novices complete 100 supervised head and neck US examinations before they are deemed competent for unsupervised practice [ 6 ]. Conversely, the European Federation for Ultrasound in Medicine and Biology suggests 300 supervised scans [ 8 ]. Yet, there is very limited evidence to support that volume is a predictor of diagnostic competence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to medical history and clinical findings, various imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound (US) are used to assess masses of unclear character in the head and neck region. US has proven to be an inexpensive, simple, and accurate real-time imaging modality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%